다중열원 열회수형 유동층 열교환기의 전열성능에 대한 실험적 연구 - 박상일(Sang-Il Park); 고창복(Chang-Bok Ko); 이영수(Young-Soo Lee) (설비공학 논문집, 29(2), 2017)
The heat transfer performance of a multi-heat-source fluidized bed heat exchanger was analyzed. The fluidized bed heat exchanger examined in this study can simultaneously recover the waste heat from gas, water vapor, and hot water. The effects of waste water flow rate, gas flow rate, and cooling water flow rate were examined to find their experimental correlations with the heat transfer coefficient. A computer program using the correlations was developed in this study to predict the thermal performance of the fluidized bed heat exchanger. The calculated heat transfer rates of gas, water vapor, waste water, and cooling water were compared with the measured values. It was found that the error of the calculated values was less than 12%.